Penerapan Metode Tanya Jawab Dalam Meningkatkan Prestasi Belajar Operasi Hitung Pada SD Negeri 014 Penghidupan - Rusaidah, Rusaidah (Komunitas Manajemen Kompetitif, 2017)
The role of teachers in educating children to be a separate problem that is in achieving the desired goal of classroom teachers, one of the less favored subjects by children where the results of pre-survey conducted in the classroom at SD N 014 Kampar living 65% of students do not like mathematics lessons about counting operations. Through classroom action research, it is obtained the result of research on the application of question and answer learning method in order to improve the result of the students 'task in class III on the mathematics subject about the number of counting operation, the result of the students' learning increased significantly. Keywords: Question and answer method, learning achievement